Minimally invasive surgery for gastric cancer: Robotic or laparoscopic? - Shuo Li; Kecheng Zhang; Lin Chen (Intelligent Surgery, 2023)
Gastric cancer surgery has developed from open surgery to laparoscopic and robotic surgery. Proper application of these technologies can better achieve function preservation, reduce postoperative complications, and improve patients' quality of life. The safety and feasibility of robotic and laparoscopic gastrectomy have been confirmed. Nevertheless, the choice of robotic surgery and laparoscopic surgery remains controversial. Discussion in this paper may provide some help to the question.